A framework of multi-agent system to facilitate security of cloud data storage - Mohamed Talib, Amir; Atan, Rodziah; Abdullah, Rusli; Azmi Murad, Masrah Azrifah (2010)
Storage in the cloud is slightly different services for slightly different needs, it’s allow users to scale storage space requirements to meet expanding requirements, improve manageability, and can be integrated easily to backup most all aspects of a businesses’ data requirements, from server to laptop. A multi-agent system (MAS) is a collection of agents that work together to achieve goal through communication and collaboration among each other. MAS are often distributed and agent has proactive and reactive features which are very useful. Cloud Computing moves the application software and databases to the large data centers, where the management of the data and services may not be fully trustworthy. In this paper, we focus on cloud data storage security, which has always been an important aspect of quality of service. To verify the correctness, integrity, confidentially and availability of users’ data in the cloud, we propose MAS framework. Considering that the data is distributed, updated, created through different sources. This research shall be carried out in five steps that defined as A Secure Software Development Life Cycle (SecSDLC) used as a research methodology. The MAS followed the Prometheus methodology Tool (PDT) for designing section. In this paper, we consider components of MAS framework, implementing a simulation framework by using JAVA and performing an input analysis of the data and an output analysis of the simulation results.